ASSESSMENT OF LEARNING USING PROBLEM-SOLVING FOR BETTER HEALTH (PSBH) AS A TOOL TO TEACH RESEARCH METHODOLOGY TO UNDERGRADUATE MEDICAL STUDENTS (Journal of Medical & Health Sciences Review, 2025)
Background: As research methodology is a theoretical subject and requires students less engagement, teaching it to undergraduate medical students is difficult. The Problem Solving for Better Health (PSBH) approach, that is the use of an interactive problem-based learning strategy, can help students to understand and apply research principles.Objective: A quantitative pre and post intervention design was conducted to ascertain if the PSBH model improved students’ understanding of research methodology.Methods: A total of 80 third-year undergraduate medical students of Rawalpindi Medical College (RMC) were selected for this study. The key research methodology concepts of problem identification, and hypothesis development in the context of study design were delivered through a consistently structured four-week PSBH module. A 25-item multiple-choice questionnaire based on a validated scale was applied before and after the intervention. Analysis of data was carried out using SPSS v25, and paired t-tests were used to assess differences in scores. Results: Mean pre-test and mean post-test scores were 52.6 ± 10.4 and 76.3 ± 8.9 respectively, p < 0.001. The results show an increase in knowledge and understanding of research methodology, when exposed to the PSBH model, is comparatively greater. Conclusion: As such, PSBH is an innovative and novel teaching approach to research methodology. It significantly improves learning outcomes through the stimulation of critical thinking, student engagement, and active learning. Given the importance of future healthcare professionals’ research competencies, it is ideal to integrate PSBH into the medical curriculum.